Revision of the genus Araneibatrus (Coleoptera: Staphylinidae: Pselaphinae) - Yin, Zi-Wei; Jiang, Ri-Xin; Steiner, Helmut (Zootaxa, 2016)
The genus Araneibatrus Yin & Li, 2010 is placed as a senior subjective synonym of Tribasodellus Nomura & Yin, 2011, syn. n., resulting in A. callissimus (Nomura & Wang, 1991) comb. n. (= Tribasodellus callissimus). A revised diagnosis and a redescription of Araneibatrus are provided, and the generic limits of Araneibatrus are re-evaluated. Four new species collected in limestone caves are described from China and Laos: A. cellulanus sp. n. (China: Guangdong), A. grossepunctatus sp. n. (China: Hunan), A. pubescens sp. n. (China: Yunnan), and A. spinosus sp. n. (Laos: Oudomxay). All six known species are diagnosed, illustrated, keyed, and mapped.